Putting a price tag on air pollution: The social healthcare costs of air pollution in France - Julia Mink (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
This study quantifies the financial burden of acute air pollution on the French healthcare system. By combining comprehensive French administrative health data for a nationally representative sample with high-resolution geospatial data on air pollution and meteorological conditions, the healthcare costs of air pollution exposure are estimated more accurately and comprehensively than in the previous literature. I use an instrumental variable approach exploiting weekly variations in local concentrations of nitrogen dioxide, ground-level ozone and particulate matter induced by variations in altitude weather conditions. I find that air pollution causes healthcare costs to the French healthcare system in the order of several billion per year, even though air pollutant concentrations are mostly below the current European air quality standards considered safe for human health. My cost estimates are about 10 times higher than those estimated in previous studies, suggesting that the health costs of air pollution have been severely underestimated. While air pollution has a large effects on overall spending in more polluted and populated urban areas due to the higher number of affected people, the marginal effects appear to be greater in lowpollution and less populated areas. Reducing population exposure even at low air pollution concentrations should therefore be an important public health goal. Even the most stringent 2021 WHO guideline values should not be considered safe for human health.
Keywords: I12; J14; Q51; Q53; 330; Air pollution; healthcare cost; instrumental variable approach